2017
DOI: 10.1016/j.diin.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Digital forensic approaches for Amazon Alexa ecosystem

Abstract: Internet of Things (IoT) devices such as the Amazon Echo -a smart speaker developed by Amazon -are undoubtedly great sources of potential digital evidence due to their ubiquitous use and their always-on mode of operation, constituting a human-life's black box. The Amazon Echo in particular plays a centric role for the cloud-based intelligent virtual assistant (IVA) Alexa developed by Amazon Lab126. The Alexa-enabled wireless smart speaker is the gateway for all voice commands submitted to Alexa. Moreover, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(77 citation statements)
references
References 9 publications
(8 reference statements)
0
72
0
5
Order By: Relevance
“…The Amazon Echo is activated by wake words like 'Alexa', but must also constantly listen for the wake-up command, and clearly this is a potential evidence source [16], [19], [24]. For example, Chung et al [25] explained how companion clients (i.e. devices used to send and capture commands and responses from intelligent home assistants, such as Alexa) can also be a source of evidence.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The Amazon Echo is activated by wake words like 'Alexa', but must also constantly listen for the wake-up command, and clearly this is a potential evidence source [16], [19], [24]. For example, Chung et al [25] explained how companion clients (i.e. devices used to send and capture commands and responses from intelligent home assistants, such as Alexa) can also be a source of evidence.…”
Section: Related Literaturementioning
confidence: 99%
“…In a prior work involving the analysis of Amazon Echo [25], it was reported that the user's history data and interactions with Alexa are stored in the SQLite database and web cache files. The authors analyzed two Amazon Echo Dots, with Android 4.4.2 + Alexa app, iOS 10.1.1 + Alexa app, OS X 10.10.5 + Chrome and Windows 10 + Chrome.…”
Section: Amazon Echo (Pi) Forensicsmentioning
confidence: 99%
“…For example, the aspect of investigating necessary user remnants for the data stored using Windows 7 and Apple iPhone on cloud services, like Dropbox, is discussed in Quick and Choo . The growing influence of DFs among researchers and practitioners in recent years have already provided new developments, innovative ideas and practices for the advancement of digital investigation in diverse areas, for example, smart TV forensics, smart home forensics, drone forensics, mobile application forensics, alexa ecosystem forensics, Internet of things device forensics, smart cities forensics, scada forensics, and so on. Le‐Khac et al discusses the recent challenges and case studies related to smart vehicle forensics.…”
Section: Background and Related Workmentioning
confidence: 99%
“…As stated, the IoT is forever expanding; this paper will look forward at ways we can question and seize evidence from new devices, as they become part of the IoT, or the future IoA. For example, the Alexa [5] enabled wireless smart speaker is a gateway for all voice commands submitted in the home. This intelligent virtual assistant interacts with a plethora of compatible IoT devices and third-party applications that leverages cloud resources [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Alexa [5] enabled wireless smart speaker is a gateway for all voice commands submitted in the home. This intelligent virtual assistant interacts with a plethora of compatible IoT devices and third-party applications that leverages cloud resources [5]. Understanding the complex cloud ecosystem that allows ubiquitous use of Alexa may be paramount for supporting IoT digital investigations in the future.…”
Section: Introductionmentioning
confidence: 99%